2021
DOI: 10.3390/nu13020529
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Modulating Activities of Olive and Its Polyphenols: A Systematic Review

Abstract: Olive oil, which is commonly used in the Mediterranean diet, is known for its health benefits related to the reduction of the risks of cancer, coronary heart disease, hypertension, and neurodegenerative disease. These unique properties are attributed to the phytochemicals with potent antioxidant activities in olive oil. Olive leaf also harbours similar bioactive compounds. Several studies have reported the effects of olive phenolics, olive oil, and leaf extract in the modulation of thyroid activities. A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…A systematic review by Pang et al showed a thyroid-protective effect of EVOO in animal models. These mechanisms are unknown, but olive oil, olive leaf extract, and olive pomace residues seem to stimulate thyroid function in euthyroid and hypothyroid animals [ 53 ].…”
Section: Mediterranean Diet and Thyroid Autoimmunitymentioning
confidence: 99%
“…A systematic review by Pang et al showed a thyroid-protective effect of EVOO in animal models. These mechanisms are unknown, but olive oil, olive leaf extract, and olive pomace residues seem to stimulate thyroid function in euthyroid and hypothyroid animals [ 53 ].…”
Section: Mediterranean Diet and Thyroid Autoimmunitymentioning
confidence: 99%
“…Many experimental studies have shown that olive derivatives, especially olive oil, have a stimulating effect on the thyroid gland (reviewed in [ 110 ]). The experimental studies were performed on various animal models: rats [ 111 , 112 , 113 , 114 ], chicken [ 115 , 116 ], lambs [ 117 ], goats [ 118 ] and calves [ 119 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…The experimental studies were performed on various animal models: rats [ 111 , 112 , 113 , 114 ], chicken [ 115 , 116 ], lambs [ 117 ], goats [ 118 ] and calves [ 119 ]. The mechanism by which olive derivatives and olive oil affect the TSH and thyroid hormone levels is still unclear [ 110 ]. To our knowledge, only one study in humans has shown the effect of olive oil consumption on thyroid hormone levels [ 120 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…On the other hand, oxidative molecules can also control the functionality of the membrane transport system through oxidative-sensitive post-translational modifications [10]. Indeed, several transporters and channels can be subjected to S-glutathionylation, nitrosylation, or carbonylation that may alter protein stability, [11][12]. In euthyroid animals, administration of olive oil or OLE increased the active triiodothyronine (T3) and the inactive thyroxine (T4) and reduced the thyroid-stimulating hormone (TSH) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several transporters and channels can be subjected to S-glutathionylation, nitrosylation, or carbonylation that may alter protein stability, [11][12]. In euthyroid animals, administration of olive oil or OLE increased the active triiodothyronine (T3) and the inactive thyroxine (T4) and reduced the thyroid-stimulating hormone (TSH) [12][13][14]. Furthermore, oral administration of EVOO improves the TSH profile and the oxidative status of the thyroid gland in a rat model of hypothyroidism [15].…”
Section: Introductionmentioning
confidence: 99%